Experiences of nurses who have children when caring for COVID-19 patients - Coskun Simsek, Didem; Gunay, Ulviye (Wiley, 2021)
Aim: This study was conducted to examine the experiences and feelings of nurses who have children when caring for patients with coronavirus disease (COVID-19). Background: The COVID-19 pandemic has affected the whole world, including Turkey where this study was conducted. Nurses are among healthcare professionals who are intensively working at the forefront during this pandemic. Countries are implementing many policies to fight this pandemic. Turkey also has implemented protective measures related to travel, sports, and cultural activities and has prohibited social meetings. Method: The study was conducted with 26 nurses working in COVID-19 clinics of two hospitals in eastern Turkey between May and July 2020 using a qualitative descriptive design. Findings: Nurses who had children longed for their children and worried about them. They were afraid of getting infected with the disease and transmitting it. Based on content analysis, the themes of the study were determined as follows: (1) longing (longing for children and longing for the pre-pandemic period), (2) fear (fear of transmitting the disease and fear of death), (3) despair, (4) concern (concern resulting from working in a different clinic, concern resulting from lack of knowledge, and concern resulting from lack of protective equipment), and (5) professional responsibility (professional awareness and love for the profession). Conclusion: Nurses were away from their families for a long time because of the fear of getting infected with COVID-19 and transmitting it. They longed for their children and experienced desperation, fear, and anxiety. They loved their profession and were not considering quitting their profession. Implications for nursing and health policy: Nurses working in COVID-19 units wear protective equipment and work for a long time under difficult conditions. In addition, nurses who have children are separated from their children because of the fear of transmitting COVID-19. Therefore, nurses caring for COVID-19 patients should alternately be replaced by nurses working in other services. They should be given the opportunity to rest and spend time with their loved ones if they are not carriers of COVID-19.
Keywords: child relations; COVID-19; family relations; mother; nursing care; pandemics; professional practice; Turkey